A novel multilayer composite structure based battery thermal management system - Kang, Chuanzhi; Yang, Jiaming; Yuan, Xiaolu; Qiu, Chenghui; Cai, Yufei (Frontiers in Energy Research, 2023)
The battery thermal management system (BTMS) utilizing phase change materials (PCM) has shown promising performance in high heat flux heat dissipation. However, conventional PCM systems do not fully exploit the latent thermal properties of paraffin wax to enhance battery cooling efficiency. To address this issue, this paper proposes a novel multilayer composite material for BTMS, aiming to improve the thermal performance of the battery and overcome the low thermal conductivity of paraffin wax. The preparation process involves positioning the battery at the center of a triangular container, melting paraffin wax and pouring it into a 100 mm high container to form a 20 mm paraffin layer, placing copper foils and graphite layers on the paraffin surface, and repeating this step once. Finally, pour the 40 mm paraffin wax into the container, resulting in a sandwich-like structure with two layers of graphite. The cooling performance of the multilayer composite structure was experimentally tested at different ambient temperatures (15°C and 20°C) and discharge rates, and compared with a conventional BTMS based on pure paraffin wax. The results demonstrate that the multilayer composite structure exhibits superior heat dissipation compared to the pure paraffin structure, significantly reducing battery temperature rise, particularly at higher discharge rates. At an ambient temperature of 20°C and a discharge rate of 5°C, the battery temperature rise is only 14.97°C, with a remarkable cooling effect of 32.6%. Moreover, optimization of the number and thickness of graphite layers in the composite structure reveals that the 6-layer graphite structure outperforms the 2-layer, 4-layer, 8-layer, and 10-layer graphite structures. Additionally, a relatively lower battery surface temperature is observed with a graphite thickness of 0.5 mm on the basis of the 6-layer graphite structure. These findings indicate that the proposed novel layout structure exhibits excellent thermal performance, effectively addressing the low thermal conductivity limitation of traditional paraffin cooling systems, and providing a new approach for thermal management of lithium batteries.